PENJERNIHAN AIR DI RT 001/RW 013 KELURAHAN PASIE NAN TIGO - Helga Yermadona; Femi Earnestly; Suryani; Firdaus (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
The water problem occurs in RT 001/RW 013 Pasie Nan Tigo Padang because they still use water ground source to fulfill their daily needs. From 30 families in RT 001/RW 013 Pasie Nan Tigo 70% of the society still have well water containing turbid, sands, and unpleasant odors. They don’t consume well water for drinking but for washing only. To fulfill their daily drinks, they must buy gallon water. Based on this problem, we offer the solution to help them to improve water sources by applying PKM (service for society) to make the procurement of clean water. Therefore, we gave them soft skill training by giving knowledge about the materials of natural and artificial purifying and hard skill training by giving the practical training about how to make the water purifying equipments. The activity focuses on the society of RT 001/RW 013 who have turbid water in their house by distributing the questionnaires before and after activity was done. The questionnaires are mostly about the society’s knowledge of water purification. There is an increasing to the society’s knowledge and skills on how to make simply water purification. The quality was increased since no turbid, no sands, and no unpleasant odors anymore after purification.